Ayurvedic Aspect of Dhatusarata &Its Clinical Significance: Life Sciences - Kisanrao Jadhao, Akanksha; Chaple, Dr. Jagruti (International Journal of Life Science and Pharma Research, 2023)
The conventional medical system known as Ayurveda was developed in India thousands of years ago. Ayurvedic specializations such as Agni, Prakruti, and Dhatusarata are the foundation for research, diagnosis, and treatment. Ayurveda states that the human body comprises Doshaa, dhatu, and mala. As Dosha is the structural and operational component of the human body, mala is to maintain the body’s health and cleanliness, and dhatu gives strength to our body. They serve as the body’s foundation. Seven dhatus are necessary for the human body’s development and survival. The term ’’SARA’’ refers to the most crucial and refined portion of dhatu. The most purified or vital part of dhatus is known as Sara. Dhatu Sara pariksha serves as a useful mirror for evaluating the characteristics and purposes of dhatus. Dhatu sarata also determines the strength of a person. The description of dhatusarata [tissue excellence] has been given under Dashavidha pariksha [tenfold examination] in Charak Samhita, Viman sthana,8th chapter. Charak says one should commit to something other than a strong or weak foundation. Instead, it depends on Sara or the superior quality of dhatus. It is proven that certain people with small frames and slim builds can be powerful. Individuals with various dhatu sarata have varying aptitudes for particular tasks. Therefore, people should select a career by determining their dhatu sarata. Some quantitative criteria must be developed to evaluate these attributes by tissue excellence or dhatu sarata. One can determine a dhatu’s true strength by evaluating Dhatu sarata. Dhatu sarata helps to determine the bala praman of an individual. For the enhancement of immunity, selection of career, antenatal care, and dietary regimen, dhatu sarata plays an important role. This study aims to elaborate on the concept of dhatu sarata and its application.